Gas processing and petroleum refining technology - Abd Hamid, Mohd. Kamaruddin (Universiti Teknologi Malaysia, 2006)
This course presents the principles and methodology for gas processing technology and petroleum refining. In particular, it provides an overall understanding of the process flow and emphasises on the principles of separation, equipment operations and equipment selection for gas processing and petroleum refining. Petroleum refining begins with the distillation, or fractionation, of crude oils into separate hydrocarbon groups. The resultant products are directly related to the characteristics of the crude processed. Most distillation products are further converted into more usable products by changing the size and structure of the hydrocarbon molecules through cracking, reforming, and other conversion processes. These converted products are then subjected to various treatment and separation processes such as extraction, hydrotreating, and sweetening to remove undesirable constituents and improve product quality. Integrated refineries incorporate fractionation, conversion, treatment, and blending operations and may also include petrochemical processing.